Strategy for respiratory exercise pattern associated with upper limb movements in COPD patients (Clinics, 2011)
INTRODUCTION: Upper limb exercises are frequently used in respiratory physiotherapy, with UL elevation and controlled inspiratory timing. However, the use of expiration during upper limb elevation appears to be a strategy that could minimize the action of accessory muscles in patients with chronic obstructive pulmonary disease. In this context, little is known about the synchrony of upper limb (UL) movements associated with breathing. The aim of this study was to investigate the respiratory pattern of chronic obstructive pulmonary disease patients during different UL exercises associated with respiratory exercises. METHODS: Fifteen chronic obstructive pulmonary disease patients participated in this study. Respiratory pattern analysis by inductance plethysmography was performed during four types of upper limb exercises, two shoulder flexion-extension (one associated with inspiratory time during the concentric phase and the other associated with expiratory time) and two shoulder abduction-adduction (same timing as above). Statistical analysis was performed by the Kolmogorov-Smirnov test and ANOVA with Tukey tests (p< 0.05). RESULTS: The thoracoabdominal coordination measurements increased in the two exercises using both inspiration during shoulder flexion (PhRIB: 172%; PhREB: 131%; PhRTB: 142% and PhAng: 238%) as well as in shoulder horizontal abduction (PhRIB: 145%; PhREB: 109%; PhRTB: 130% and PhAng: 229%), differing from the exercises with expiration at the time of shoulder flexion and horizontal abduction. CONCLUSION: The exercises performed with inverted respiratory time produced less asynchrony and can be used as important strategies during physical exercise programs in these patients.